Spinal epidural and synovial lipomatosis in a 3‐year‐old Eurasian dog receiving sustained steroid therapy. Issue 4 (22nd June 2022) - Signoret, Marion; Gros, Lucile; Dumont, Renaud; Dally, Claire; Le Boedec, Kevin; Cauzinille, Laurent
Abstract: This report describes a spinal cord epidural and synovial lipomatosis in a 3‐year‐old neutered male Eurasian dog. This dog presented for ambulatory paraparesis and was previously treated with immunosuppressive dosages of prednisolone for 2 years. Computed tomography (CT) myelography and magnetic resonnance imaging (MRI) images identified dorsal compression of the thoraco‐lumbar spinal cord by hypertrophic epidural fat. Histological examination identified extensive well‐differentiated mature adipose tissue in the subepithelial area of the tarsal synovium. Prednisolone is a reported predisposing factor in humans with lipomatosis. Abstract : This report describes spinal epidural and synovial lipomatosis in a 3‐year‐old neutered male Eurasian dog. This dog presented for ambulatory paraparesis and was previously treated with immunosuppressive dosages of prednisolone for 2 years. Computed tomography (CT) myelography and magnetic resonnance imaging (MRI) images identified dorsal compression of the thoraco‐lumbar spinal cord by hypertrophic epidural fat. Histological examination identified expensive well‐differentiated mature adipose tissue in the subepithelial area of the tarsal synovium. Prednisolone is a reported predisposing factor in humans with lipomatosis.